The Impact of Literal Translation from French in Articles from the Journal “Al-Mutarjim” (1) – Samples from Issues 02, 06, 08, and 10 - daas, YAHIA (El Omda in Linguistics and Discourse Analysis, 2022)
Violating the Arab style in the writings of many researchers influenced by the literal trans- lation of French language is a phenomenon that contributed to the abandonment of the arabic addition which is of focal concern treated in this article.This phenomenon is apparently due to the problematic of translation in the arab world; it is not transmiting from foreign languages into arabic abiding by the requirements of the Arabic style; hasting as such to literaly translate, the back door of the car as:"الباب الخلفيّ للسيّارة" instead of "بابُ السيارةِ الخلفيُّ". Accordingly, we have chosen samples of articles from four issues of the "AL-MUTARGIM review, issued by the teaching lab of translation at the university of Oran. The linguistic reality is that the authors of these articles do not translate, but rather employ methods rejected by classical arabic, stressing the violation of the arabic addition.